Pengelolaan Perpustakaan Madrasah di Kota Palangka Raya (Studi terhadap Upaya Madrasah Menjadikan Perpustakaan Sebagai Sumber Belajar dan Bagian dari Sistem Pengajaran) - Usman Usman; Siti Narani (Institut Agama Islam Negeri Salatiga, 2020)
The role of the madrasah library is not just infrastructure that must be available at the madrasah, but also must be managed properly according to standards and can truly function as a learning resource that can meet information for students and educators that ultimately can improve student competency and quality of the process of education and teaching in madrasah. Madrasah libraries in the city of Palangka Raya are still far from expectations, many libraries are managed only to meet the availability of infrastructure in madrasah. But there are still not many who manage the library properly to be used as a source of learning and part of the teaching system in the madrasah, therefore the purpose of this study is to find out how the efforts of the madrasah library make the library as a learning resource and part of the teaching system which includes development plans madrasah library, library staff development program, collection development and management activities, infrastructure development, service systems used and library programs in increasing the use of libraries in madrasah.This research is a field research with a qualitative descriptive approach. The respondents in this study were madrasah library managers and there were 11 madrasah that were sampled from 35 madrasah in Palangka Raya City.The results of this study are, madrasah efforts to make libraries as a source of learning and teaching system in madrasah from the aspect of planning, madrasah libraries do not have a strategic plan and grand design related to library development, madrasah libraries still get minimal budget for collection development and some even no, there are still many library management personnel who are not yet professional, infrastructure facilities that are not yet standard, the service system is still manual and information technology has not been maximally applied. While the efforts made by the madrasah for the use of the library by teachers and students are the movement of reading 15 minutes before learning or during breaks in the library, distributing a collection of library books in every reading corner in the class, giving rewards to students who frequently visit the library, inviting students to visit Other libraries, film screenings in the library and holding collection display cabinets in the school grounds.